A small-molecule inhibitor of MDMX suppresses cervical cancer cells via the inhibition of E6-E6AP-p53 axis - Jingwen Zhang; Guohua Yu; Yanting Yang; Yingjie Wang; Mengqi Guo; Qikun Yin; Chunhong Yan; Jingwei Tian; Fenghua Fu; Hongbo Wang (Elsevier, 2022)
Dysfunction of p53 is observed in many malignant tumors, which is related to cancer susceptibility. In cervical cancer, p53 is primarily degradated through the complex of high-risk human papillomaviruses (HPV) oncoprotein E6 and E6-associated protein (E6AP) ubiquitin ligase. What is less clear is the mechanism and role of murine double minute X (MDMX) in cervical carcinogenesis due to the inactive status of murine double minute 2 (MDM2). In the current study, XI-011 (NSC146109), a small-molecule inhibitor of MDMX, showed robust anti-proliferation activity against several cervical cancer cell lines. XI-011 promoted apoptosis of cervical cancer cells via stabilizing p53 and activating its transcription activity. Moreover, XI-011 inhibited the growth of xenograft tumor in HeLa tumor-bearing mice, as well as enhanced the cytotoxic activity of cisplatin both in vitro and in vivo. Interestingly, MDMX co-localized with E6AP and seems to be a novel binding partner of E6AP to promote p53 ubiquitination. In conclusion, this work revealed a novel mechanism of ubiquitin-dependent p53 degredation via MDMX-E6AP axis in cervical carcinogenesis, and offered the first evidence that MDMX could be a viable drug target for the treatment of cervical cancer.